EDUCATION CHILD IN A FAMILY OF SURAH AN-NISA’ VERSE 9 PERSPECTIVE - Yessy Gusminalita; Doli Witro; Kesi Afrilia (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2020)
In family that plays an important role in shaping the child's personality is the parent. The personality is obtained through the educational process taught by his parents. First and foremost educators for children in the family are parents because it is from them that the child first gets an education. In essence, education in the family occurs implicitly, starting with communication between family members and the daily behavior of their parents. In addition to good communication, the behavior of both parents also participate in the formation of children’s morals. Because the family is the first and primary madrasa for a child. In general, in a family environment, religious values are instilled in children to shape their behavior. Therefore, religious education in the family environment is needed to find out which boundaries are good and bad in children's daily lives. In Islam it is taught to protect the family (or children) from ignorance, even it is highly recommended not to leave the family in a weak state (educational and economic). As explained in the Qur’an surah an-Nisa’ verse 9. This paper will discuss education in the family perspective of surah an-Nisa’ verse 9. This is important to discuss to avoid the birth of a generation of the weak, both weak in education and economically. With an education in the family, it is expected to form a strong generation is facing the challenges of the times ahead.